2009
DOI: 10.1097/naq.0b013e3181accabc
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Benefits of Expressive Writing in an Electronic Format

Abstract: Expressive writing is recognized as having therapeutic benefits including fewer stress-related visits to the doctor, improved immune system functioning, reduced blood pressure, improved functional status, fewer days in the hospital, feelings of greater psychological well-being, reduced depressive symptoms, fewer posttraumatic intrusion and avoidance symptoms, improved memory and sleep, and faster healing after surgery. Combine this with current popularity of social networking, and there is a formula for improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Danoff-Burg and colleagues (2010) found that a higher level of narrative, compared to emotionality, is associated with greater mental health gains, and just as with emotional writing, narrative writing can lower perceived stress and depressive symptoms. With regard to blogging, Atkinson and coworkers (2009) posited that the beneficial outcomes associated with expressive writing combined with the increased prominence of online social networking presents a promising opportunity for future research and clinical work. A recent study of blogging for cancer patients found that the process enabled patients to reconstruct their life story and fostered feelings of closure and an expectation that they would be remembered after their death (Chiu & Hsieh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Danoff-Burg and colleagues (2010) found that a higher level of narrative, compared to emotionality, is associated with greater mental health gains, and just as with emotional writing, narrative writing can lower perceived stress and depressive symptoms. With regard to blogging, Atkinson and coworkers (2009) posited that the beneficial outcomes associated with expressive writing combined with the increased prominence of online social networking presents a promising opportunity for future research and clinical work. A recent study of blogging for cancer patients found that the process enabled patients to reconstruct their life story and fostered feelings of closure and an expectation that they would be remembered after their death (Chiu & Hsieh, 2012).…”
Section: Introductionmentioning
confidence: 99%